Sistem Pembelajaran E-learning Berbasis Web - Kusumaningrum, Ratih; , Nurgiyatna, M.Sc, Ph.D (2016)
Advancement of education will affect significantly for the progress of nation, in particular the progress of science and technology. Implementation effort of technology especially communication of information in the field of education one of them is a learning system using the internet or commonly known as e-learning. With e-learning can provide easiness in obtaining learning material without paying, hone skill with some exercise and easier to interact with teacher anywhere and anytime. Development methods that used to by the author is waterfall method in this research. Waterfall method is a method that use to a systematic approach, and sort start form the level of defining the system requirement to maintenance. Waterfall method has 6 phases, namely requirement specification, architectural design, coding, integration & testing, operation & maintenance. Result of this research is more than 80% of respondents state this system is easy to use, this system has a complete menu, and this system can use to study at home, and more than 75% respondents state this system can improve the quality of study. With those conclusion, the purpose of this research have been achieved. Keyword : Learning system, E-learning, Web.